Encapsulated in sediments: eDNA deciphers the ecosystem history of one of the most polluted European marine sites. (February 2023) - Barrenechea Angeles, Ines; Romero-Martínez, Maria Lorena; Cavaliere, Marco; Varrella, Stefano; Francescangeli, Fabio; Piredda, Roberta; Mazzocchi, Maria Grazia; Montresor, Marina; Schirone, Antonio; Delbono, Ivana; Margiotta, Francesca; Corinaldesi, Cinzia; et al.
Highlights: Tracing the 200-year history of anthropogenic impacts using ancient sedimentary DNA. Holistic overview of marine biodiversity changes ranging from prokaryotes to multicellular organisms. Sedimentary DNA analysis provides insight into preindustrial reference conditions. Abstract: The Anthropocene is characterized by dramatic ecosystem changes driven by human activities. The impact of these activities can be assessed by different geochemical and paleontological proxies. However, each of these proxies provides only a fragmentary insight into the effects of anthropogenic impacts. It is highly challenging to reconstruct, with a holistic view, the state of the ecosystems from the preindustrial period to the present day, covering all biological components, from prokaryotes to multicellular eukaryotes. Here, we used sedimentary ancient DNA ( sedaDNA ) archives encompassing all trophic levels of biodiversity to reconstruct the two century-natural history in Bagnoli-Coroglio (Gulf of Pozzuoli, Tyrrhenian Sea), one of the most polluted marine-coastal sites in Europe. The site was characterized by seagrass meadows and high eukaryotic diversity until the beginning of the 20th century. Then, the ecosystem completely changed, with seagrasses and associated fauna as well as diverse groups of planktonic and benthic protists being replaced by low diversity biota dominated by dinophyceans and infaunal metazoan species. The sedaDNA analysis revealed a five-phase evolution of the area, where changes appear as the result of a multi-level cascade effect of impacts associated with industrial activities, urbanization, water circulation and land-use changes. The sedaDNA allowed to infer reference conditions that must be considered when restoration actions are to be implemented.